The D-Dimer to Albumin Ratio Could Predict Hospital Readmission Within One Year in Patients with Acute Exacerbation of Chronic Obstructive Pulmonary Disease - Li L; Feng Q; Yang C (International Journal of COPD)
Li Li, Qinsheng Feng, Chunsong Yang Department of Respiratory and Critical Care Medicine, Baise People’s Hospital, Baise, Guangxi, 533099, People’s Republic of ChinaCorrespondence: Li Li, Department of Respiratory and Critical Care Medicine, Baise People’s Hospital, No. 8, Chengxiang Road, Youjiang District, Baise, Guangxi, 533099, People’s Republic of China, Tel +86-0776-2851142, Email llidoctorICU@outlook.comPurpose: To explore the association of D-dimer-to-albumin ratio (DAR) with hospital readmission within one year in patients with acute exacerbation chronic obstructive pulmonary disease (AECOPD).Patients and Methods: From January 2019 to October 2022, 509 patients with COPD were enrolled in Baise People’s Hospital for this retrospective cohort study. Baseline data and blood samples were collected, and patients were followed up for one year after inclusion. The AECOPD hospital readmission within one year was the outcome. Receiver operating characteristics (ROC) curves were conducted to determine the prognostic performance of DAR for predicting readmission within one year. The relationships between DAR, neutrophil-to-lymphocyte ratio (NLR), and AECOPD hospital readmission were conducted using univariate and multivariate logistic regression models, with odds ratios (ORs) and 95% confidence intervals (CIs). The relationship was further explored in different modified Medical Research Council (mMRC), COPD assessment test (CAT), COPD course, pneumonia, glucocorticoid, antibiotic subgroups.Results: Totally, 117 (22.99%) COPD patients were hospital readmission due to AECOPD. The area under the curve (AUC) for the DAR was 0.726. DAR ≥ 2.21 (OR=1.80, 95% CI: 1.05– 3.17) was associated with elevated odds of AECOPD hospital readmission within one year. DAR ≥ 2.21 was related to increased odds of AECOPD hospital readmission in patients of those mMRC ≥ 2, CAT > 20, COPD course < 10 years, and pneumonia. NLR ≥ 3.69 was associated with higher odds of AECOPD hospital readmission in patients of those mMRC ≥ 2 and COPD course ≥ 10 years.Conclusion: In patients with AECOPD, DAR showed a better predictive value in predicting the risk of hospital readmission in patients with AECOPD within one year. The findings of our study might help identify patients with a high risk of readmission within one year and provide timely treatment to prevent the reoccurrence of AECOPD.Keywords: acute exacerbation, chronic obstructive pulmonary disease, readmission, D-dimer to albumin ratio